REKAYASA TABLET EFFERVESCENT DARI TOMAT DAN DAUN KELOR DENGAN PERBEDAAN RASIO ASAM DAN BASA - Umar Hafidz Asy'ari Hasbullah; Finda Evita Marviana; Alpin Hidayatulloh; Tania Widiastuti (AGROINTEK, 2022)
This study aimed to produce the best formulation in the manufacture of effervescent derived from tomatoes and Moringa leaves with different acid-base ratio treatments. Tomato and Moringa leaves were converted into powdered extracts to be formulated with citric acid, sodium bicarbonate, PVP, mannitol, and aspartame. The ratios of citric acid and sodium bicarbonate as treatments were 3:5, 4:5, and 5:5. The results showed that the formulation with an acid:base ratio (5:5) had the potential to be developed and refined before being commercialized. This formulation was chosen because it has the sensory profile with a sweet, slightly sour and fresh taste profile, the lowest Moringa leaf aroma, the color of the clear solution was slightly green and slightly orange. This formulation was made from a composition of 12.5% tomato extract powder, 7.5% Moringa leaf extract powder, 34% citric acid, 34% sodium bicarbonate, 7.5% mannitol, 3% PVP, and 1.5% aspartame. Tablet was carried out in a room with a temperature of 18℃ with a RH of 45-58%.